Engineering Behavior of Swelling Soil Treated by Tyre Ash - Mohammed Fadhel, Abbas; ., Shayal; Mohammed, Hadi; ., Mohamed; Khdhar, Mohamed (International Journal of Engineering and Technology, 2018)
Swelling soils in arid and semi-arid climates are well known to cause detrimental damages in the form of cracks and differential movements of the civil engineering structures. For efficient and economical methods to reduce mitigation of swelling soils, there is a growing interest in using waste materials with a recycling it and using for improving soil properties . This work focused on using (tyre ash) as a reinforced for improving the swelling soil. Using the tire ash in soil improvement can be a feasible target for recycling this waste material, hence decreasing the pollution problems. An experimental program was conducted to determine the geotechnical characteristics of the swelling soil, including Atterberger limits ,Compaction, California Bearing Ratio and strength characteristics. Different percentages of tyre ash (5%, 10%, and 15%) were mixed with original swelling soil to calculate its influence on geotechnical properties. The experimental results displayed that 15% tyre ash reduced the plasticity and density considerably. Finally, the results show that improvement of swelling soils using tyre ash properly be an efficient technique in improvement the soil characteristics against swelling-shrinking potential of ground soils on which pavements and light weight structures are constructed. Therefore, the scrap tire rubber waste has a potential for improving swelling soils, thus giving a two advantages in enhancing a problematic soil and also resolving the problem of disposal of waste by recycling it. On the other hand, the results of axial compressive strength and California Bearing Ratio tests demonstrated that the amounts of tyre ash could enhanced theÂ shear strength properties of soil.Â Â